Positive electrode for secondary battery and secondary battery

The positive electrode for secondary batteries, featuring lithium transition metal composite oxide with high Ni content, carbon fibers, and surface-modified alkaline earth metal elements, addresses capacity degradation issues by ensuring conductivity and preventing particle cracking, thus maintaining battery performance.

JP2025061474AInactive Publication Date: 2025-04-10PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2025007400
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-03-31
Filing Date
2025-01-20
Publication Date
2025-04-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Lithium transition metal composite oxides with high Ni content used as positive electrode active materials in secondary batteries experience capacity degradation due to charge and discharge cycles.

Method used

A positive electrode for secondary batteries is designed with a lithium transition metal composite oxide containing 80 mol% or more of Ni, along with carbon fibers having an outermost circumference diameter of 20 nm or less, and an alkaline earth metal element present on the surface of the oxide particles, ensuring a conductive path and modifying the particle surface to prevent cracking.

Benefits of technology

The proposed positive electrode structure effectively suppresses the capacity decrease associated with charge/discharge cycles, maintaining battery performance by enhancing conductivity and preventing particle cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025061474000002
    Figure 2025061474000002
  • Figure 2025061474000001
    Figure 2025061474000001
Patent Text Reader

Abstract

To suppress the capacity decrease involved in the charge / discharge cycle of a secondary battery by using a positive electrode for the secondary battery containing a lithium transition metal composite oxide with a high Ni content.SOLUTION: A positive electrode for a secondary battery according to the present disclosure includes a positive electrode current collector and a positive electrode mixture layer disposed on the positive electrode current collector. The positive electrode mixture layer includes a positive electrode active material containing a lithium transition metal composite oxide and carbon fibers having an outermost diameter of 20 nm or less. The lithium transition metal composite oxide contains 80 mol % or more of Ni, Co, and Al relative to the total number of moles of metal elements excluding Li. Alkaline earth metal elements are present on the particle surfaces of the oxide. The content of the carbon fibers is 0.01 mass% or more and 1.0 mass% or less relative to the total amount of the positive electrode active material.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a positive electrode for a secondary battery and a secondary battery. [Background technology]

[0002] In recent years, lithium transition metal composite oxides with a high Ni content have been attracting attention as a positive electrode active material with high energy density. For example, Patent Document 1 describes a positive electrode active material that is mainly composed of Ni and Li and has the general formula Li x Ni 1-p-q-r Co p Al q A r O 2-y (A is at least one element selected from the group consisting of Ti, V, In, Cr, Fe, Sn, Cu, Zn, Mn, Mg, Ga, Ni, Co, Zr, Bi, Ge, Nb, Ta, Be, Ca, Sr, Ba, and Sc) and a nonaqueous electrolyte secondary battery containing a composite oxide composed of single-crystal primary particles having an average particle size of 2 μm to 8 μm. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2006-54159 A Summary of the Invention [Problem to be solved by the invention]

[0004] When a lithium transition metal composite oxide with a high Ni content is used as a positive electrode active material, a decrease in capacity due to charge / discharge cycles of the secondary battery becomes a problem. [Means for solving the problem]

[0005] A positive electrode for a secondary battery according to one embodiment of the present disclosure includes a positive electrode current collector and a positive electrode mixture layer disposed on the positive electrode current collector, the positive electrode mixture layer including a positive electrode active material containing a lithium transition metal composite oxide and carbon fibers having an outermost diameter of 20 nm or less, the lithium transition metal composite oxide containing 80 mol % or more of Ni, Co, and Al relative to the total number of moles of metal elements excluding Li, alkaline earth metal elements being present on the particle surfaces of the oxide, and the content of the carbon fibers being 0.01 mass % or more and 1 mass % or less relative to the total amount of the positive electrode active material.

[0006] A secondary battery according to one aspect of the present disclosure includes a positive electrode and a negative electrode, and the positive electrode is the above-described positive electrode for a secondary battery. Effect of the Invention

[0007] By using the positive electrode for a secondary battery according to the present disclosure, it is possible to suppress the decrease in capacity that accompanies the charge / discharge cycles of the secondary battery. [Brief description of the drawings]

[0008] [Figure 1] 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery according to an embodiment; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] A positive electrode for a secondary battery according to one embodiment of the present disclosure includes a positive electrode current collector and a positive electrode mixture layer disposed on the positive electrode current collector, the positive electrode mixture layer including a positive electrode active material containing a lithium transition metal composite oxide and a carbon fiber having an outermost diameter of 20 nm or less, the lithium transition metal composite oxide containing 80 mol% or more of Ni relative to the total number of moles of metal elements excluding Li, an alkaline earth metal element is present on the particle surface of the oxide, and the content of the carbon fiber is 0.01 mass% or more and 1 mass% or less relative to the total amount of the positive electrode active material. According to the present disclosure, the alkaline earth metal element present on the particle surface of the lithium transition metal composite oxide suppresses, for example, a side reaction between the non-aqueous electrolyte of the secondary battery and the lithium transition metal composite oxide, so that the particle surface of the lithium transition metal composite oxide is modified, and the inhibition of lithium ion movement and the occurrence of particle cracking are suppressed. According to the present disclosure, the positive electrode mixture layer contains the above-mentioned amount of carbon fibers having an outermost diameter of 20 nm or less, thereby, for example, ensuring a conductive path in the positive electrode mixture layer. The positive electrode for secondary batteries according to the present disclosure uses a lithium transition metal composite oxide with a high Ni content, and the synergistic effect of the surface modification of particles, the suppression of particle cracking, and the securing of a conductive path in the positive electrode mixture layer is thought to suppress the capacity decrease associated with the charge / discharge cycles of the secondary battery.

[0010] Hereinafter, embodiments of the positive electrode for secondary batteries and secondary batteries according to the present disclosure will be described in detail with reference to the drawings. In this specification, the expression "numerical value (1) to numerical value (2)" means numerical value (1) or more and numerical value (2) or less.

[0011] FIG. 1 is a cross-sectional view of a secondary battery as an example of an embodiment. The secondary battery 10 shown in FIG. 1 includes a wound electrode body 14 formed by winding a positive electrode 11 and a negative electrode 12 with a separator 13 interposed therebetween, a non-aqueous electrolyte, insulating plates 18 and 19 respectively arranged above and below the electrode body 14, and a battery case 15 for accommodating the above-mentioned members. The battery case 15 is composed of a bottomed cylindrical case body 16 and a sealing body 17 for closing an opening of the case body 16. Note that, instead of the wound electrode body 14, an electrode body of another form may be applied, such as a laminated electrode body formed by alternately stacking positive and negative electrodes with a separator interposed therebetween. In addition, examples of the battery case 15 include a metallic case having a cylindrical shape, a square shape, a coin shape, a button shape, etc., and a resin case (laminated battery) formed by laminating a resin sheet.

[0012] The case body 16 is, for example, a cylindrical metal container with a bottom. A gasket 28 is provided between the case body 16 and the sealing body 17 to ensure airtightness inside the battery. The case body 16 has a protruding portion 22 that supports the sealing body 17, for example, a part of the side surface of the case body 16 protruding inward. The protruding portion 22 is preferably formed in an annular shape along the circumferential direction of the case body 16, and supports the sealing body 17 on its upper surface.

[0013] The sealing body 17 has a structure in which a filter 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cap 27 are laminated in this order from the electrode body 14 side. Each member constituting the sealing body 17 has, for example, a disk shape or a ring shape, and each member except the insulating member 25 is electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected to each other at their respective centers, and the insulating member 25 is interposed between each of their peripheral edges. When the internal pressure of the secondary battery 10 increases due to heat generation caused by an internal short circuit or the like, for example, the lower valve body 24 deforms and breaks so as to push the upper valve body 26 toward the cap 27, and the current path between the lower valve body 24 and the upper valve body 26 is interrupted. When the internal pressure further increases, the upper valve body 26 breaks, and gas is discharged from the opening of the cap 27.

[0014] In the secondary battery 10 shown in Fig. 1, a positive electrode lead 20 attached to the positive electrode 11 passes through a through hole in an insulating plate 18 and extends toward the sealing body 17, and a negative electrode lead 21 attached to the negative electrode 12 passes outside an insulating plate 19 and extends toward the bottom side of the case body 16. The positive electrode lead 20 is connected to the underside of a filter 23, which is the bottom plate of the sealing body 17, by welding or the like, and a cap 27, which is the top plate of the sealing body 17 and is electrically connected to the filter 23, serves as a positive electrode terminal. The negative electrode lead 21 is connected to the inner bottom surface of the case body 16 by welding or the like, and the case body 16 serves as a negative electrode terminal.

[0015] The positive electrode 11, the negative electrode 12, the separator 13, and the non-aqueous electrolyte that constitute the secondary battery 10 will be described in detail below.

[0016] [Positive electrode] The positive electrode 11 includes a positive electrode current collector and a positive electrode mixture layer formed on the positive electrode current collector. For the positive electrode current collector, a foil of a metal such as aluminum or an aluminum alloy that is stable in the potential range of the positive electrode, or a film having the metal disposed on the surface layer, can be used. The positive electrode mixture layer is configured to include, for example, a positive electrode mixture containing a positive electrode active material, a binder, a conductive agent, etc. The positive electrode mixture layer is preferably formed on both sides of the positive electrode current collector. The positive electrode 11 can be manufactured, for example, by applying a slurry of a positive electrode mixture containing a positive electrode active material, a binder, a conductive agent, etc. onto the positive electrode current collector, drying and rolling the coating, and forming a positive electrode mixture layer on both sides of the positive electrode current collector.

[0017] The conductive agent contained in the positive electrode mixture layer includes carbon fibers having an outermost diameter (fiber diameter) of 20 nm or less. The content of the carbon fibers is 0.01 mass% or more and 1 mass% or less, preferably 0.01 mass% or more and 0.5 mass% or less, based on the total amount of the positive electrode active material. The carbon fibers include known materials used as conductive agents in batteries, such as carbon nanotubes (CNTs), carbon nanofibers (CNFs), vapor grown carbon fibers (VGCFs), electrospun carbon fibers, polyacrylonitrile (PAN)-based carbon fibers, and pitch-based carbon fibers.

[0018] It is believed that the inclusion of the carbon fibers having an outermost diameter of 20 nm or less in the positive electrode mixture layer in the above-mentioned predetermined amount ensures a conductive path in the positive electrode mixture layer and contributes to suppressing the capacity decrease due to charge / discharge cycles. If the carbon fiber content is less than 0.01 mass%, the conductive path in the positive electrode mixture layer is not sufficiently ensured, and if the carbon fiber content is more than 1 mass%, the movement of the nonaqueous solvent and electrolyte in the positive electrode mixture layer is easily hindered, and in either case, the capacity decrease due to charge / discharge cycles is not suppressed.

[0019] The outermost diameter of the carbon fibers is preferably 1 nm or more and 20 nm or less, and more preferably 1.5 nm or more and 10 nm or less, in terms of, for example, improving the electrical conductivity of the carbon fibers themselves and ensuring a conductive path of the positive electrode mixture layer by adding a small amount of carbon fibers due to the improved electrical conductivity, etc. The outermost diameter of the carbon fibers can be determined by measuring the outer diameters of any 50 carbon fibers using a field emission scanning microscope (FE-SEM) or a transmission electron microscope (TEM) and taking the arithmetic average.

[0020] The fiber length of the carbon fibers is, for example, preferably 0.1 μm or more and 20 μm or less, more preferably 1 μm or more and 10 μm or less, and more preferably 1 μm or more and 5 μm or less, in order to ensure a conductive path between active materials in the positive electrode mixture layer. The fiber length of the carbon fibers can be determined by measuring the lengths of 50 arbitrary carbon fibers using a field emission scanning electron microscope (FE-SEM) and taking the arithmetic average.

[0021] Among the carbon fibers exemplified above, it is preferable that the carbon fiber contains a carbon nanotube, for example, in terms of further suppressing the capacity decrease accompanying the charge / discharge cycle. Examples of the carbon nanotube include a single-walled carbon nanotube, a double-walled carbon nanotube, and a multi-walled carbon nanotube. A single-walled carbon nanotube (SWCNT) is a carbon nanostructure in which one layer of graphene sheets forms one cylindrical shape, a double-walled carbon nanotube is a carbon nanostructure in which two layers of graphene sheets are stacked concentrically to form one cylindrical shape, and a multi-walled carbon nanotube is a carbon nanostructure in which three or more layers of graphene sheets are stacked concentrically to form one cylindrical shape. The graphene sheet refers to a layer in which the carbon atoms of the sp2 hybrid orbital that constitutes the crystal of graphite (graphite) are located at the vertices of a regular hexagon. The shape of the carbon nanotube is not limited. Examples of such shapes include various forms including a needle shape, a cylindrical tube shape, a fishbone shape (fishbone or cup stack type), a playing card shape (platelet), and a coil shape.

[0022] The carbon nanotubes contained in the positive electrode mixture layer preferably include single-walled carbon nanotubes. In general, single-walled carbon nanotubes form a conductive path in the positive electrode mixture layer in a smaller amount than multi-walled carbon nanotubes, so it is considered that the movement of the non-aqueous solvent and electrolyte in the positive electrode mixture layer is facilitated by including a small amount of single-walled carbon nanotubes in the positive electrode mixture layer. The positive electrode mixture layer may include not only single-walled carbon nanotubes but also double-walled carbon nanotubes or multi-walled carbon nanotubes.

[0023] The positive electrode active material contained in the positive electrode mixture layer contains a lithium transition metal composite oxide. The lithium transition metal composite oxide contains 80 mol% or more of Ni with respect to the total number of moles of metal elements excluding Li. Further, an alkaline earth metal element is present on the particle surface of the lithium transition metal composite oxide. The alkaline earth metal element present on the particle surface is, for example, in the state of a compound such as a metal, an alloy, or an oxide. The particle surface refers to the primary particle surface or the secondary particle surface. Note that a part of the alkaline earth metal element may be present inside the primary particles of the lithium transition metal composite oxide and may form a solid solution with other metal elements contained in the lithium transition metal composite oxide. Hereinafter, this lithium transition metal composite oxide may be referred to as composite oxide A.

[0024] The alkaline earth metal element refers to the elements in Group 2 of the periodic table, and examples include beryllium, magnesium, calcium, strontium, barium, and radium. The presence of this alkaline earth metal element on the particle surface of composite oxide A is considered to suppress the modification of the particle surface of composite oxide A and particle cracking due to side reactions with the non-aqueous electrolyte, and contribute to the suppression of capacity degradation associated with charge-discharge cycles.

[0025] Composite oxide A is, for example, in terms of increasing the high energy density of the battery and suppressing the capacity degradation of the battery in charge-discharge cycles, a general formula excluding the alkaline earth metal element present on the particle surface of composite oxide A is Li y Ni (1-x) M x O2 (where 0 ≦ x ≦ 0.2, 0 < y ≦ 1.2, and M is one or more elements selected from Co, Al, Mn, Fe, Ti, Sr, Ca, and B) is preferable. In terms of increasing the capacity of the battery, etc., y in the above general formula preferably satisfies 0.95 ≦ y < 1.05, and more preferably satisfies 0.97 ≦ a ≦ 1.03. Further, for example, in terms of suppressing the degradation of the battery capacity in charge-discharge cycles, etc., M in the above general formula is preferably one or more elements selected from Co, Al, and Mn.

[0026] The content of Ni in the composite oxide A is preferably 85 mol% or more, more preferably 90 mol% or more, based on the total number of moles of metal elements excluding Li, from the viewpoint of, for example, increasing the capacity of the battery. In the case of the above general formula, x in the formula preferably satisfies x≦0.15, more preferably satisfies x≦0.1. In addition, the content of Ni in the composite oxide A is preferably 98 mol% or less, more preferably 95 mol% or less, based on the total number of moles of metal elements excluding Li, from the viewpoint of, for example, suppressing the capacity decrease associated with charge / discharge cycles. In the case of the above general formula, x in the formula preferably satisfies 0.02≦x, more preferably satisfies 0.05≦x.

[0027] The alkaline earth metal element present on the particle surface of the composite oxide A preferably contains at least one of calcium (Ca) and strontium (Sr) in terms of suppressing capacity loss due to charge / discharge cycles, etc. The content of the alkaline earth metal element present on the particle surface and inside the particle of the composite oxide A is preferably in the range of 0.01 mol % to 10 mol %, more preferably in the range of 0.1 mol % to 5 mol %, based on the total number of moles of metal elements excluding Li.

[0028] The molar fraction of metal elements in the entire particle (particle surface and interior) of complex oxide A is measured by an inductively coupled plasma atomic emission spectrometry (ICP-AES), an electron probe microanalyzer (EPMA), an energy dispersive X-ray spectrometer (EDX), etc. The state of alkaline earth metals present on the surface of complex oxide A can be confirmed by, for example, exposing the cross section of complex oxide A with high precision using a polishing device such as an ion milling cross-section polisher, and then measuring it with EDX, etc.

[0029] The composite oxide A is a particle having a volume-based median diameter (D50) of, for example, 3 μm to 30 μm, preferably 5 μm to 25 μm, and particularly preferably 7 μm to 15 μm. D50 means a particle diameter at which the cumulative frequency is 50% from the smallest particle diameter in the volume-based particle size distribution, and is also called the median diameter. The particle size distribution of the composite oxide A is measured by a laser diffraction type particle size distribution measuring device (for example, MT3000II manufactured by Microtrack Bell Co., Ltd.).

[0030] The composite oxide A can be prepared, for example, by the following procedure.

[0031] The method for producing the composite oxide A includes, for example, a first step of obtaining a transition metal oxide containing Ni and an arbitrary metal element, a second step of mixing the transition metal oxide obtained in the first step with a Li compound and a compound containing an alkaline earth metal element to obtain a mixture, and a third step of firing the mixture.

[0032] In the first step, for example, while stirring a solution of a metal salt containing Ni and an arbitrary metal element (Co, Al, Mn, etc.), an alkaline solution such as sodium hydroxide is dropped to adjust the pH to the alkaline side (e.g., 8.5 to 12.5), thereby precipitating (co-precipitating) a transition metal hydroxide containing Ni and the arbitrary metal element. Then, the transition metal hydroxide is calcined to obtain a transition metal oxide containing Ni and the arbitrary metal element. The calcination temperature is not particularly limited, but is, for example, in the range of 300°C to 600°C.

[0033] In the second step, the transition metal oxide obtained in the first step, a Li compound, and a compound containing an alkaline earth metal element are dry-mixed to obtain a mixture. Examples of Li compounds include Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, and LiF. Examples of compounds containing an alkaline earth metal element include hydroxides, oxides, carbonates, sulfates, and nitrates of alkaline earth metal elements. Examples of Ca include Ca(OH)2, CaO, CaCO3, CaSO4, and Ca(NO3)2. Examples of Sr include Sr(OH)2, Sr(OH)2·8H2O, SrO, SrCO3, SrSO4, and Sr(NO3)2. The mixing ratio of the transition metal oxide obtained in the first step and the Li compound is preferably, for example, such that the molar ratio of metal elements other than Li:Li is in the range of 1:0.98 to 1:1.1. The mixing ratio of the transition metal oxide obtained in the first step and the compound containing an alkaline earth metal element is preferably, for example, such that the molar ratio of metal elements other than Li:alkaline earth metal element is in the range of 1:0.0001 to 1:0.05. In the second step, when mixing the transition metal oxide obtained in the first step, the Li compound, and the compound containing an alkaline earth metal element, other metal raw materials may be added as necessary. The other metal raw materials are oxides containing metal elements other than the metal elements constituting the transition metal oxide obtained in the first step, etc.

[0034] In the third step, the mixture obtained in the second step is preferably fired at 850°C or less for a predetermined time. In addition, the firing of the mixture in the third step is preferably performed as a multi-stage firing process including a first firing step in which the mixture is fired in a firing furnace under an oxygen stream at a first heating rate to a first set temperature of 450°C to 680°C, and a second firing step in which the fired product obtained in the first firing step is fired in a firing furnace under an oxygen stream at a second heating rate to a second set temperature of more than 680°C to 850°C. Here, the first heating rate is in the range of 1.5°C / min to 5.5°C / min, and the second heating rate is slower than the first heating rate and is preferably in the range of 0.1°C / min to 3.5°C / min. Note that the first heating rate and the second heating rate may be set in a plurality of rates for each temperature range as long as they are within the ranges specified above. The holding time of the first set temperature in the first firing step is preferably 5 hours or less, more preferably 3 hours or less. The holding time of the first set temperature refers to the time during which the first set temperature is maintained after the first set temperature is reached. The holding time of the second set temperature in the second firing step is preferably 1 hour to 10 hours, more preferably 1 hour to 5 hours. The holding time of the second set temperature refers to the time during which the second set temperature is maintained after the second set temperature is reached. When firing the mixture, for example, it is carried out in an oxygen stream with an oxygen concentration of 60% or more, and the flow rate of the oxygen stream is set to 10 cm / s of the firing furnace. 3 The flow rate can be in the range of 0.2 mL / min to 4 mL / min per kg of mixture and 0.3 L / min or more per kg of mixture.

[0035] The content of the composite oxide A is preferably 90 mass % or more, and more preferably 99 mass % or more, based on the total mass of the positive electrode active material, from the viewpoint of improving the battery capacity, etc. The positive electrode active material may contain a lithium transition metal composite oxide having a composition different from that of the composite oxide A.

[0036] The positive electrode mixture layer may contain a particulate conductive agent, but preferably does not contain a particulate conductive agent. When the positive electrode mixture layer does not contain a particulate conductive agent, the loading amount of the positive electrode active material is increased, and the energy density of the battery may be improved. Examples of the particulate conductive agent include carbon materials such as carbon black, acetylene black, ketjen black, and graphite. When a particulate conductive agent is used, it is preferable that the primary particle diameter is 5 nm or more and 100 nm or less.

[0037] Examples of the binder contained in the positive electrode mixture layer include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, carboxymethylcellulose (CMC) or a salt thereof, and polyethylene oxide (PEO).

[0038] The amount of the positive electrode mixture layer disposed on the positive electrode current collector is set to 250 g / m in order to increase the energy density of the battery. 2 According to this embodiment, the amount of the positive electrode mixture layer disposed on the positive electrode current collector is preferably 250 g / m or more. 2 Even in the above case, the effect of suppressing the capacity decrease due to the charge / discharge cycles is achieved.

[0039] [Negative electrode] The negative electrode 12 has a negative electrode current collector and a negative electrode mixture layer provided on the surface of the negative electrode current collector. For the negative electrode current collector, a foil of a metal such as copper that is stable in the potential range of the negative electrode 12, a film with the metal disposed on the surface layer, or the like can be used. The negative electrode mixture layer is composed of, for example, a negative electrode mixture containing a negative electrode active material and a binder. The negative electrode 12 can be produced, for example, by applying a slurry of a negative electrode mixture containing a negative electrode active material and a binder to the surface of the negative electrode current collector, drying the coating, and then rolling to form a negative electrode mixture layer on both sides of the negative electrode current collector. For example, the binder may be the same as that of the positive electrode 11.

[0040] The negative electrode active material is not particularly limited as long as it can reversibly occlude and release lithium ions, and examples thereof include carbon materials, Si-containing materials, Sn-containing materials, Li-Ti-containing materials, and the like. From the viewpoint of increasing the capacity of the battery, Si-containing materials are preferred. Examples of the Si-containing materials include Si-containing compounds represented by SiO x (0.5 ≦ x ≦ 1.6), Li 2y SiO (2+y) Si-containing compounds in which Si particles are dispersed in a lithium silicate phase represented by (0 < y < 2), Si-containing compounds in which Si particles are dispersed in a carbon phase, and the like. Further, in terms of, for example, increasing the capacity of the battery and suppressing a decrease in capacity accompanying charge and discharge cycles, it is preferable to use a Si-containing material and a carbon material in combination. Examples of the carbon material include graphite, graphitizable carbon (soft carbon), non-graphitizable carbon (hard carbon), and the like. Among them, graphite, which is excellent in charge-discharge stability and has a small irreversible capacity, is preferred. Examples of the graphite include natural graphite such as flake graphite, massive graphite, and earthy graphite, artificial massive graphite, and artificial graphite such as graphitized mesophase carbon microbeads.

[0041] [Separator] For the separator 13, for example, a porous sheet having ion permeability and insulation is used. Specific examples of the porous sheet include microporous thin films, woven fabrics, non-woven fabrics, and the like. As the material of the separator 13, polyolefins such as polyethylene and polypropylene, cellulose, and the like are suitable. The separator 13 may have either a single-layer structure or a laminated structure. A heat-resistant layer or the like may be formed on the surface of the separator 13.

[0042] [Non-aqueous electrolyte] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt. The non-aqueous electrolyte is not limited to a liquid electrolyte, and may be a solid electrolyte using a gel-like polymer or the like. For the electrolyte salt, for example, lithium salts such as LiFSI, LiTFSI, LiBF4, and LiPF6 are used. For the solvent, for example, esters such as ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl acetate (MA), and methyl propionate (MP), ethers, nitriles, amides, and mixed solvents of two or more of these are used. The non-aqueous solvent may contain a halogen-substituted product in which at least a part of the hydrogen of the above-mentioned solvents is substituted with a halogen atom such as fluorine.

[0043] Examples of the halogen-substituted product include fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates, and fluorinated chain carboxylates such as methyl fluoropropionate (FMP). EXAMPLES

[0044] The present disclosure will be further described below with reference to examples, but the present disclosure is not limited to these examples.

[0045] <Example 1> [Preparation of composite oxide A] Ni 0.90 Co 0.5 Al 0.05The transition metal oxide and Sr(OH)2 were mixed so that the Sr content was 1.0 mol% relative to the total amount of Ni, Co, and Al of the transition metal oxide represented by O2, and lithium hydroxide monohydrate (LiOH·H2O) was further mixed so that the molar ratio of Li to the total amount of Ni, Co, Al, and Sr was 1:1.03. The mixture was fired under an oxygen stream with an oxygen concentration of 95% (flow rate of 10 L / min per 1 kg of the mixture) at a heating rate of 2°C / min from room temperature to 650°C, and then fired at a heating rate of 1°C / min from 650°C to 800°C. Impurities were removed from this fired product by washing with water to obtain a composite oxide A. This was used as the positive electrode active material of Example 1.

[0046] [Preparation of positive electrode] The positive electrode active material, carbon nanotubes (having an outermost diameter (φ) of 1.5 nm and a fiber length (L) of 5 μm) as a conductive agent, and polyvinylidene fluoride (PVdF) were mixed in a solid content mass ratio of 100:0.05:1.0, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added, followed by kneading to prepare a positive electrode mixture slurry. The positive electrode mixture slurry was applied to both sides of a positive electrode current collector made of aluminum foil, and the coating film was dried. The coating film was then rolled using a roller and cut to a predetermined electrode size to obtain a positive electrode in which a positive electrode mixture layer was formed on both sides of the positive electrode current collector. The amount of the positive electrode mixture layer on the positive electrode current collector was 300 g / m 2 It was.

[0047] [Preparation of negative electrode] Graphite, which is a negative electrode active material, SiO, sodium carboxymethylcellulose, and styrene-butadiene rubber were mixed in a mass ratio of 95:5:1:1, and an appropriate amount of water was added to prepare a negative electrode mixture slurry.

[0048] [Preparation of non-aqueous electrolyte] Ethylene carbonate (EC), methyl ethyl carbonate (MEC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 3:3:4. Lithium hexafluorophosphate (LiPF6) was dissolved in the mixed solvent to a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.

[0049] [Preparation of test cell] The positive electrode and the negative electrode were stacked facing each other with a separator interposed therebetween, and the stack was wound to prepare an electrode assembly. The electrode assembly was then housed in a cylindrical battery case body with a bottom, and the nonaqueous electrolyte was poured into the battery case body. The opening of the battery case body was then sealed with a gasket and a sealing member to prepare a test cell.

[0050] <Example 2> Ni 0.90 Co 0.05 Al 0.05 A composite oxide A was prepared in the same manner as in Example 1, except that a transition metal oxide and Ca(OH)2 were mixed so that the Ca content was 1.0 mol% relative to the total amount of Ni, Co, and Al of the transition metal oxide represented by O2, and lithium hydroxide monohydrate (LiOH·H2O) was further mixed so that the molar ratio of Li to the total amount of Ni, Co, Al, and Ca was 1:1.03. This composite oxide A was used as the positive electrode active material of Example 5, and a test cell was prepared in the same manner as in Example 1, except that the positive electrode active material, carbon nanotubes (with an outermost diameter (φ) of 1.5 nm and a fiber length (L) of 5 μm) as a conductive agent, and polyvinylidene fluoride (PVdF) were mixed in a solid content mass ratio of 100:0.05:1.0.

[0051] <Example 3> In preparing the positive electrode, the composite oxide A of Example 2 was used as the positive electrode active material, and this positive electrode active material was mixed with carbon nanotubes (having an outermost diameter (φ) of 8 nm and a fiber length (L) of 2 μm) as a conductive agent and polyvinylidene fluoride (PVdF) in a solid content mass ratio of 100:0.5:1.0. A test cell was prepared in the same manner as in Example 2.

[0052] <Example 4> In the preparation of the positive electrode, the composite oxide A of Example 3 was used as the positive electrode active material, and this positive electrode active material was mixed with carbon nanotubes (having an outermost diameter (φ) of 8 nm and a fiber length (L) of 2 μm) as a conductive agent and polyvinylidene fluoride (PVdF) in a solid content mass ratio of 100:0.5:1.0, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added, followed by kneading to prepare a positive electrode mixture slurry. The positive electrode mixture slurry was applied to both sides of a positive electrode current collector made of aluminum foil, and the coating was dried. The coating was then rolled using a roller and cut to a predetermined electrode size to obtain a positive electrode in which a positive electrode mixture layer was formed on both sides of the positive electrode current collector. The amount of the positive electrode mixture layer on the positive electrode current collector was 250 g / m 2 A test cell was prepared in the same manner as in Example 2, except that:

[0053] <Example 5> Ni 0.88 Co 0.10 Al 0.02 A composite oxide A was prepared in the same manner as in Example 4, except that a transition metal oxide and Sr(OH)2 were mixed so that the Sr content was 1.0 mol% relative to the total amount of Ni, Co, and Al of the transition metal oxide represented by O2, and lithium hydroxide monohydrate (LiOH·H2O) was further mixed so that the molar ratio of Li to the total amount of Ni, Co, Al, and Ca was 1:1.03. This composite oxide A was used as the positive electrode active material of Example 5, and a test cell was prepared in the same manner as in Example 1, except that the positive electrode active material, carbon nanotubes (with an outermost diameter (φ) of 1.5 nm and a fiber length (L) of 5 μm) as a conductive agent, and polyvinylidene fluoride (PVdF) were mixed in a solid content mass ratio of 100:0.05:1.0.

[0054] <Comparative Example 1> A test cell was prepared in the same manner as in Example 1, except that in preparing the composite oxide A, Sr(OH)2 was not added.

[0055] <Comparative Example 2> A test cell was prepared in the same manner as in Example 1, except that in the preparation of composite oxide A, Sr(OH)2 was not added, and in the preparation of the positive electrode, the above positive electrode active material, carbon nanotubes (having an outermost diameter (φ) of 8 nm and a fiber length (L) of 2 μm) serving as a conductive agent, and polyvinylidene fluoride (PVdF) were mixed in a solid content mass ratio of 100:0.5:1.0.

[0056] <Comparative Example 3> A test cell was prepared in the same manner as in Example 1, except that in preparing the positive electrode, the positive electrode active material, acetylene black (having an average particle size (φ) of approximately 30 nm) as a conductive agent, and polyvinylidene fluoride (PVdF) were mixed in a solid content mass ratio of 100:1.0:1.0.

[0057] <Comparative Example 4> A test cell was prepared in the same manner as in Example 2, except that in preparing the positive electrode, the positive electrode active material, acetylene black (having an average particle size (φ) of approximately 30 nm) as a conductive agent, and polyvinylidene fluoride (PVdF) were mixed in a solid content mass ratio of 100:1.0:1.0.

[0058] <Comparative Example 5> A test cell was prepared in the same manner as in Example 5, except that in preparing the positive electrode, the positive electrode active material, acetylene black (having an average particle size (φ) of approximately 30 nm) as a conductive agent, and polyvinylidene fluoride (PVdF) were mixed in a solid content mass ratio of 100:1.0:1.0.

[0059] [Charge / discharge cycle test] Each test cell of the Examples and Comparative Examples was charged at a constant current of 0.5 It in a temperature environment of 25° C. until the battery voltage reached 4.2 V, and then charged at a constant voltage until the current value reached 1 / 100 It at 4.2 V. Thereafter, constant current discharge was performed at a constant current of 1 It until the battery voltage reached 2.5 V. This charge / discharge cycle was repeated 100 times.

[0060] For each test cell of the examples and comparative examples, the discharge capacity at the first cycle and the discharge capacity at the 100th cycle of the cycle test were determined, and the capacity retention rate was calculated by the following formula. The results are shown in Table 1.

[0061] Capacity retention rate (%) = (100th cycle discharge capacity ÷ 1st cycle discharge capacity) × 100

[0062] [Table 1]

[0063] In both the Examples and Comparative Examples, composite oxide A having a high Ni content was used as the positive electrode active material. However, the test cells of Examples 1 to 5 had a higher capacity retention rate after the charge-discharge cycle test than the test cells of Comparative Examples 1 to 5, and the capacity decrease due to the charge-discharge cycle was suppressed. [Explanation of symbols]

[0064] 10 secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 15 battery case, 16 case body, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 protruding portion, 23 filter, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cap, 28 gasket.

Claims

1. a positive electrode current collector; and a positive electrode mixture layer disposed on the positive electrode current collector, The positive electrode mixture layer includes a positive electrode active material including a lithium transition metal composite oxide and a carbon fiber having an outermost peripheral diameter of 20 nm or less, The lithium transition metal composite oxide contains 80 mol % or more of Ni, Co, and Al based on the total number of moles of metal elements excluding Li, and an alkaline earth metal element is present on the particle surface of the oxide, A content of the carbon fiber is 0.01% by mass or more and 1.0% by mass or less with respect to a total amount of the positive electrode active material.

2. 2. The positive electrode for a secondary battery according to claim 1, wherein a ratio of said Ni in said lithium transition metal composite oxide is 90 mol % or more with respect to a total number of moles of metal elements excluding Li.

3. A secondary battery comprising a positive electrode and a negative electrode, the positive electrode being the positive electrode for a secondary battery according to claim 1 or 2.

Citation Information

Patent Citations

  • Positive active material for lithium secondary battery, its manufacturing method, and lithium secondary battery

    JP2009032467A

  • Conductive assistant for lithium secondary battery electrode, conductive assistant fluid dispersion for lithium secondary battery electrode including the same, and positive electrode for lithium secondary battery

    JP2013062236A

  • Nonaqueous electrolyte secondary battery

    JP2016031881A

  • Lithium ion secondary battery

    WO2018051667A1

  • Positive electrode composition for lithium ion secondary batteries, positive electrode for lithium ion secondary batteries, and lithium ion secondary battery

    WO2019073830A1